Railroad workers on strike: domination and resistence relationships in RVPSC (Revista de História Regional, 2007)
In this article we analyze the main strikes carried out by the railroad workers of the Rede de Viação Paraná-Santa Catarina (RVPSC) in the first half of 20th Century. As an integrant part of the process of social relations of domination and resistance, the strike is the result of the conjunction of the interests of the railroad workers from experiences lived in common, for this reason the study about the strike allows us to glimpse diverse characteristics of the world of the work in the railroad.